YouTube Content Production for Arabic Language Learning: Cross-National Study - Segaf Baharun; Nur Hanifansyah; Moh. Tohiri Habib; Ahmad Arifin; Muhammad Syaifullah; Nur Aina Faqihah (CV FOUNDAE, 2026)
This study employs a mixed-methods approach to examine the pedagogical value of learner-generated YouTube videos in Arabic language instruction in Islamic senior secondary schools across Malaysia and Indonesia. The study involved 240 non-native Arabic learners, with 120 participants from each country, and investigated the impact of video production on Arabic language proficiency, learner autonomy, and digital literacy over a sixteen-week period. Quantitative data were collected through standardized pre–post proficiency tests, autonomy and digital literacy scales, while multimodal content analysis was conducted on 240 purposively selected videos from a validated corpus of 600 YouTube uploads that followed structured production cycles. The findings revealed statistically significant improvements in overall Arabic language proficiency in Malaysia (d = 0.86) and Indonesia (d = 0.76), with particularly strong gains in speaking skills in Malaysia (d = 1.04) and Indonesia (d = 0.94). Learner autonomy and digital literacy competencies also showed significant improvement. Regression analysis indicated that production frequency and participation in feedback processes significantly predicted improvements in speaking proficiency and learner autonomy. The content analysis identified cultural vlogs, language tutorials, and narrative storytelling as the dominant genres, reflecting sociocultural influences across contexts. The study proposes a data-informed model of digital content creation integrating sociocultural interaction, multiliteracies, and self-regulated learning in Arabic CALL contexts